Recent advances in understanding GLP-1R (glucagon-like peptide-1 receptor) function. (29th January 2013) - Koole, Cassandra; Pabreja, Kavita; Savage, Emilia E.; Wootten, Denise; Furness, Sebastian G.B.; Miller, Laurence J.; Christopoulos, Arthur; Sexton, Patrick M.
Abstract : Type 2 diabetes is a major global health problem and there is ongoing research for new treatments to manage the disease. The GLP-1R (glucagon-like peptide-1 receptor) controls the physiological response to the incretin peptide, GLP-1, and is currently a major target for the development of therapeutics owing to the broad range of potential beneficial effects in Type 2 diabetes. These include promotion of glucose-dependent insulin secretion, increased insulin biosynthesis, preservation of β-cell mass, improved peripheral insulin sensitivity and promotion of weight loss. Despite this, our understanding of GLP-1R function is still limited, with the desired spectrum of GLP-1R-mediated signalling yet to be determined. We review the current understanding of GLP-1R function, in particular, highlighting recent contributions in the field on allosteric modulation, probe-dependence and ligand-directed signal bias and how these behaviours may influence future drug development.